Employer Branding Phenomenon: A Systematic Review Conceptualization at Higher Education Institutions - Annisa Ciptagustia; Syamsul Hadi Senen; Kusnendi Kusnendi (West Science Social and Humanities Studies, 2023)
This research aims to uncover the dimensions of employer branding (EB) that attract and retain employees working at the university, both lecturers and education personnel. This research uses a systematic literature review with the PRISMA diagram. The database used comes from Scopus and Emerald with journal criteria, open access, English language, obtained 6 articles to be analyzed. The dimensions used are social values, development values, diversity, economic values, interest values, reputation values, working environment values, and work life balance. Some use Reward strategy, People orientedness, Leadership development to measure employer branding. In addition, it uses the EB dimension of employee retention and employee attraction. This study examines the object of employer branding research in higher education related to exploring the dimensions of the perspective of academic workers including lecturers and education personnel. In addition, it finds the grand theory used in constructing employer branding.